2012
DOI: 10.1103/physrevlett.108.268304
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relaxations of Thin Polymer Films

Abstract: Time-dependent changes of thermodynamic properties due to structural relaxations and physical aging occur in all glasses. We show that the physical aging of thin supported films of star-shaped macromolecules, with f arms of length N(arm), exhibits average aging dynamics that are sensitive to f and N(arm). Regions of the films in proximity to interfaces age at substantially different rates than the interior of the film; this is also true of linear chain systems. This behavior may be reconciled in terms of a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
85
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 32 publications
8
85
1
Order By: Relevance
“…6,19,20 However Tgsurf became gradually lower than Tgbulk as M w arm became much larger than M e, the molecular weight between entanglements; this trend is consistent with the behavior of linear chain polymers. 6,19,20 Molecular dynamics simulations revealed that this behavior– Tgsurf>Tgbulk-might be due to positional correlations of the star-shaped molecular at the free surface of the film. 20 In this letter we demonstrate using XPCS that the in contrast to the linear chain polymers, the free surface layer relaxations are slow compared to the bulk and this persists to temperatures T > T g + 50 K. Molecular dynamics simulations of supported thin polymer films indicate that the slow dynamics, and Tgsurf>Tgbulk, would be due to a preferential localization of these molecules at the free surface.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…6,19,20 However Tgsurf became gradually lower than Tgbulk as M w arm became much larger than M e, the molecular weight between entanglements; this trend is consistent with the behavior of linear chain polymers. 6,19,20 Molecular dynamics simulations revealed that this behavior– Tgsurf>Tgbulk-might be due to positional correlations of the star-shaped molecular at the free surface of the film. 20 In this letter we demonstrate using XPCS that the in contrast to the linear chain polymers, the free surface layer relaxations are slow compared to the bulk and this persists to temperatures T > T g + 50 K. Molecular dynamics simulations of supported thin polymer films indicate that the slow dynamics, and Tgsurf>Tgbulk, would be due to a preferential localization of these molecules at the free surface.…”
supporting
confidence: 75%
“…Tgsurf>Tgbulk. 6,19,20 However Tgsurf became gradually lower than Tgbulk as M w arm became much larger than M e, the molecular weight between entanglements; this trend is consistent with the behavior of linear chain polymers. 6,19,20 Molecular dynamics simulations revealed that this behavior– Tgsurf>Tgbulk-might be due to positional correlations of the star-shaped molecular at the free surface of the film.…”
supporting
confidence: 65%
“…This is consistent with findings of previous experimental studies. 37,57 At this point, it is important to note that this effect is not due to the increased free volume caused by an increased number of free-ends into the system. If that would be true, then decreasing the length of the arms would further decrease T c iso , which is not consistent to our findings as presented above.…”
Section: Core Particlementioning
confidence: 96%
“…Another element tuning aging rates of thin polymer films is the molecular architecture. The aging rate of star‐shaped PS thin films on silicon oxide is reduced compared with its linear counterpart, and physical aging is also suppressed with reducing the degree of polymerization per arm in thin films of star‐shaped PS 105…”
Section: Polymer Nanoparticles: Our Recent Contributionsmentioning
confidence: 99%